ANALISIS YURIDIS HUBUNGAN KERJA TENAGA MEDIS (DOKTER) DENGAN RUMAH SAKIT(STUDI KASUS PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR : 36 K/Pdt.Sus-PHI/2023) - Andi Kinang; Rumainur (JOURNAL OF LAW AND NATION, 2024)
This case focuses on the dispute over whether the employment relationship between medical personnel/doctors and hospitals is an employment relationship based on an employment agreement or a partnership agreement, which has an impact on legal protection for medical personnel/doctors. This decision emphasizes the importance of clarity on the status of the employment relationship between medical personnel/doctors and hospitals in determining the rights of medical personnel/doctors, including wages, benefits, and social and legal protection. The problem in this study is more about how the legal regulations and Settlement of Industrial Relations Disputes between medical personnel/doctors and hospitals and how the case of the position of legal protection and Settlement of Industrial Relations Disputes of medical personnel/doctors and legal considerations of the Supreme Court of the Republic of Indonesia based on the decision of case Number 36 K/Pdt.Sus-PHI/2023 in providing legal certainty regarding the employment relationship of medical personnel/doctors with hospitals in the future. The writing method used in this study is normative juridical, namely a literature study with the process of collecting materials, data and materials containing the employment relationship between medical personnel, doctors and hospitals. Based on the research results, it was concluded that the working relationship between medical personnel/doctors and hospitals can be in the form of a working relationship or a cooperative relationship as a hospital partner, which affects the rights and obligations of each party.Keywords: Legal certainty, work partner relations, doctors and hospitals.